Effectiveness of sanitizing agents in inactivating Escherichia coli (ATCC 25922) in food cutting board surfaces. Removal E. coli using different sanitizers - CEZAR AUGUSTO BELTRAME; EDUARDA BOFF MARTELO; RAIZA DE ALMEIDA MESQUITA; IEDA ROTTAVA; JULIANA BARBOSA; CLARICE STEFFENS; GECIANE TONIAZZO; EUNICE VALDUGA; ROGERIO LUIS CANSIAN (Chiriotti Editori, 2016)
The objective of this study was to investigate Escherichia coli adhesion on new and used polyethylene cutting board surface and evaluate it's removal using different sanitizer (peracetic acid, chlorhexidine, sodium hypochlorite and organic acids). Results indicated that the number of adherent cells increased with time in both surfaces evaluated. Evaluating the sanitizer action, 0.5% peracetic acid was more effective in removal E. coli than chlorhexidine and organic acids at same concentration in both surfaces. Peracetic acid and sodium hypochlorite also showed effectiveness at concentrations of 0.2% and 0.5% on new surfaces, respectively. 0.8% of chlorhexidine and 2.0% of organic acids showed similar effectiveness in the removal E. coli on new and used surfaces, respectively. These results suggest that peracetic acid is considerable promise sanitizer for application in surfaces of the food processing industry.